2005
DOI: 10.1038/sj.pcan.4500848
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of QM protein expression correlates with tumor grade in prostatic adenocarcinoma

Abstract: The QM protein is a transcription cofactor inhibiting the activity of AP-1 transcription factors and is also a ribosomal protein participating in protein synthesis. While protein synthesis is known to be increased in many cancers, inhibition of AP-1 activity presumably suppresses development and growth of sex-hormone-regulated tumor cells. The present study is the first report on immunohistochemical data of QM in human prostatic tissues. Paraffin sections of human prostate cancer samples were immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…The RPL10 is also a tumor suppressor gene and the protein it encodes is known as the tumor suppression protein QM[24]. Reduced RPL10 expression is associated with increasing grade of prostatic adenocarcinoma[25]. Primers specific to RPL10L and RPL39L were used to screen for expression of these testis specific retrogenes in a panel of ovarian cancers (Table 2; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The RPL10 is also a tumor suppressor gene and the protein it encodes is known as the tumor suppression protein QM[24]. Reduced RPL10 expression is associated with increasing grade of prostatic adenocarcinoma[25]. Primers specific to RPL10L and RPL39L were used to screen for expression of these testis specific retrogenes in a panel of ovarian cancers (Table 2; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the importance of ribosome function and translational control in tumorigenesis has been underscored although several oncogenes, such as Myc [25], and tumor suppressor genes, such as PTEN [26] and p53 [27], have been linked to direct regulation of ribosome production and protein translation. In prostate cancer patients, reduced expression of RPL10 has been suggested to associate with early development of the cancer; however, high expression of RPL10 at later stages of cancer development could drive forward to a more aggressive phenotype [28]. More importantly, mutations in RPL10 gene have been recently detected in cancer patients who are unrelated to any heritable diseases [29].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the decrease in QM protein level, determined by immunohistochemistry, is associated with tumor grade of prostate cancer. 26 Together, these results suggest that QM or a gene at the Xq28 may be a tumor suppressor gene, and its decreased expression could be due to alterations at the genetic level (such as LOH or MSI), transcriptional level or translational level and could be related to the development of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%